PROPOSING AN INTEGRATIVE-PROGRESSIVE MODEL IN HANDLING TROUBLED INDONESIAN OVERSEAS WORKERS IN THE TRANSIT AREA (A SOCIO-LEGAL RESEARCH IN TANJUNG PINANG CITY, KEPULAUAN RIAU PROVINCE) - Shahrullah, Rina Shahriyani; Syarief, Elza (UI Scholars Hub, 2015)
Tanjung Pinang City of the Riau Islands Province (Provinsi Kepulauan Riau) is a transit area for the troubled Indonesian overseas workers from Singapore and Malaysia. The Indonesian National Board for the Placement and Protection of Indonesian Workers (Badan Nasional Penempatan dan Perlindungan Tenaga Kerja Indonesia/BNP2TKI) reported that 15,105 troubled Indonesian overseas workers were deported from January to November 2014 via Tanjung Pinang City. Previous research revealed that citizens of Tanjung Pinang City criticized the treatments given by the local government to the deported workers by reason that they were not the citizens of the Riau Islands Province, yet the local government has to provide shelters and funds prior to returning them to their home towns. The treatments for the deported workers in the transit area have also raised pros and cons among the stakeholders who are in charge of handling the deported workers. This circumstance may not occur if a special regional regulation of the Riau Islands Province has been issued to govern the troubled Indonesian overseas workers in the transit area. Due to this vacuum of law, this research aims to establish a mechanism in handling the deported workers in the transit area by designing an integrative-progressive model which can be adopted by the stakeholders. The model is to link the legal and non- legal issues and as well as to provide the collaborative mechanisms for the stakeholders based on the approaches of the integrative and progressive legal theory.